Digital Pilgrimage: The Role of Online Platforms in Preserving and Promoting Kampung Dukuh’s Religious Heritage - Lahpan, Neneng Yanti Khozanatu; Putra, Bagas Dwipantara; Hidayana, Iip Sarip; Budiman, Arif (Mudra : jurnal seni budaya, 2025)
Kampung Adat Dukuh is a traditional village that maintains its ancestors’ traditions and cultural values, especially from Islamic teachings. This traditional village receives regular visits from pilgrims every Saturday. Continuous visits by outsiders to this area have given rise to various potential socio-cultural vulnerabilities among the indigenous community. Therefore, an effort is needed to manage the visits of these pilgrims as a potential for well-managed religious tourism that can control the boundaries that maintain the sustainability and comfort of the lives of indigenous people. One of them is developing a digital platform to promote the richness of the traditions and culture of Dukuh Village while maintaining its values by properly documenting them following the etiquette in Dukuh Village. This article aims to see the changes and potential for empowering Dukuh Village as a religious tourism destination and disseminating information about its cultural practices through digital platforms. By using qualitative methods and developing the PAR (Participatory Action Research) method combined with ethnographic work, this study pays attention to community involvement in this empowerment. The study results show that the young generation of Kampung Dukuh has a solid ability to adapt and learn by making the digital platform a space for expression and maintaining the values of the wisdom of Kampung Dukuh by presenting accurate information using an insider perspective.